The clinical significance of BRAF and NRAS mutations in a clinic‐based metastatic melanoma cohort. (31st October 2013) - Ekedahl, H.; Cirenajwis, H.; Harbst, K.; Carneiro, A.; Nielsen, K.; Olsson, H.; Lundgren, L.; Ingvar, C.; Jönsson, G.
Abstract : What's already known about this topic? BRAF and NRAS mutations occur frequently in melanoma tumours. BRAF and NRAS mutations are associated with certain clinical and histopathological characteristics. Treatment with BRAF inhibitors improves survival in generalized melanoma. What does this study add? There is high consistency in BRAF and NRAS mutation status between paired metastases. We show differences in clinical outcome in relation to BRAF and NRAS status in patients with distant metastatic disease. We confirm the effect of a BRAF inhibitor in a single clinical institution. Summary: Background: BRAF and NRAS mutations are frequently found in melanoma tumours, and recently developed BRAF‐targeted therapies demonstrate significant clinical benefit. Objectives: We sought to investigate the clinical significance of BRAF and NRAS mutations in a clinic‐based metastatic melanoma cohort. Methods: In total, 237 tumours, mostly metastatic lesions, from 203 patients were screened for mutations in exon 15 of BRAF and exon 2 of NRAS using Sanger sequencing. BRAF and NRAS mutation status was analysed in relation to clinical and histopathological characteristics, and outcome. Results: Mutation in BRAF and NRAS was present in 43% (88% V600E, 10% V600K) and 30% (48% Q61K, 40% Q61R) of metastatic melanomas, respectively. We found consistent BRAF and NRAS mutation status in all but one of 27 patients with multiple metastases. BRAF mutation was associated with younger age at primary diagnosis ( P = 0·02). Among patients with distant metastatic melanoma, patients with BRAF ‐mutant tumours without BRAF inhibitor treatment had inferior survival compared with patients with BRAF inhibitor treatment [hazard ratio (HR) 2·35, 95% confidence interval (CI) 1·10–5·01, P = 0·03]. We also observed a trend towards better prognosis for patients with wild‐type and NRAS ‐mutant tumours compared with BRAF V600E‐mutant tumours (HR 0·64, 95% CI 0·39–1·04, P = 0·07; and HR 0·76, 95% CI 0·48–1·21, P = 0·25, respectively). Conclusions: We were able to confirm the effect of BRAF inhibitor treatment in a single clinical institution. The results suggest further that BRAF mutation is a weak prognostic factor but a strong predictive factor and that BRAF ‐mutant melanoma might constitute one or more distinct subtypes of the disease with certain aetiology and clinical outcome.